Single photon emission tomography using 99mTc-HM-PAO in the investigation of dementia. Issue 9 (September 1987) - Neary, D; Snowden, J S; Shields, R A; Burjan, A W; Northen, B; MacDermott, N; Prescott, M C; Testa, H J
Abstract : Single photon emission tomographic imaging of the brain using 99mTc HM-PAO was carried out in patients with a clinical diagnosis of Alzheimer's disease, non-Alzheimer frontal-lobe dementia, and progressive supranuclear palsy. Independent assessment of reductions in uptake revealed posterior hemisphere abnormalities in the majority of the Alzheimer group, and selective anterior hemisphere abnormalities in both other groups. The findings were consistent with observed patterns of mental impairment. The imaging technique has potential value in the differential diagnosis of primary cerebral atrophy.